Patriarchy, Abortion, and the Criminal System: policing Female Bodies - Chesney-Lind, Meda (Women & criminal justice, 2017)
This paper argues for a broader consideration of the issue of abortion—one that stresses the centrality of the denial of reproductive rights in the patriarchal policing of women’s bodies and their sexuality. Globally, the estimates of abortion-related deaths in 2014 ranged from 22,500 to 44,000, and countless women are injured or left infertile by seeking illegal abortions. We briefly review international trends regarding abortion politics and then analyze closely women’s access to abortion in two countries: the United States and Bangladesh. Representing two very different contexts of the developed and the developing world, respectively, we contend that abortion services are being constrained by misogynistic politics that deny women control over their bodies. Finally, the paper reviews recent international efforts to establish abortion rights as part of a broader landscape of human rights. Notably, while there are some efforts in the global north to recriminalize both contraception and abortion, these practices have been characterized by a recent United Nation’s report as the deliberate denial of medically available and necessary services and hence a form of “torture.”